2021
DOI: 10.1016/j.eujim.2021.101308
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 lockdown on physical activity and sedentary behaviors in French children and adolescents: New results from the ONAPS national survey

Abstract: Introduction In France March 14, 2020 a national lockdown was imposed in France for 55 days to prevent the spread of the Covid-19 and all schools were closed. This study aimed to investigate the effects of home confinement as a result of  lockdown on the activity (physical activity and sedentary behaviors), and their determinants, on French children (6-10 years) and adolescents (11-17 years). Methods The National Observatory for Physical Activity and Sedentary behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
84
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 25 publications
17
84
0
7
Order By: Relevance
“…The Figure 2 illustrates these changes among children and adolescents 6 to 17 years old who were initially active and inactive. Concerning screen time, 62% of 6-10 year old children and 68.9% of adolescents experienced an increase in exposure to screens 38 .…”
Section: Movement Behavior In French Childrenmentioning
confidence: 98%
“…The Figure 2 illustrates these changes among children and adolescents 6 to 17 years old who were initially active and inactive. Concerning screen time, 62% of 6-10 year old children and 68.9% of adolescents experienced an increase in exposure to screens 38 .…”
Section: Movement Behavior In French Childrenmentioning
confidence: 98%
“…Canada 5-to 11-years 95% of children not meeting guidelines for physical activity due to sedentary behaviour including screen time (Moore et al, 2020) China 6-to 17-years 30 hours more screen time per week (Xiang et al, 2020) France 6-to 10-years 62% of children had increased screen time (Chambonniere et al, 2021) (Pagani et al, 2013). On the other hand, a recent meta-analysis found that while increased screen time was associated with lower language skills, quality screen time (educational programs) and caregiver scaffolding during screen time was associated with stronger language skills in children under twelve years of age (Madigan et al, 2019).…”
Section: Age Screen Time Effectmentioning
confidence: 99%
“…The negative effects of lockdown on physical activity and sedentary attitudes were linked to changes in lifestyle behaviours during the lockdown era, according to this report. These indings should be taken into account in future public health policies (Chambonniere et al, 2021). As a result, the lockdown time is strongly linked to a decrease in overall physical activity.…”
Section: Resultsmentioning
confidence: 99%